2003
DOI: 10.1007/bf02465505
|View full text |Cite
|
Sign up to set email alerts
|

Zur Mauser des Großgefieders beim Seeadler (Haliaeetus albicilla) in Schleswig-Holstein

Abstract: Flight feather moult of White-tailed Eagle (Haliaeetus albicilla) in Schleswig-Holstein, GermanyBetween 1955 and 2000 feathers moulted by White-tailed Eagles were collected systematically in the breeding territories in Schleswig-Holstein, Germany. 581 tail feathers and 382 primaries from a maximum of 22 nest sites (1999) and more than 300 secondaries (8 ! collected between 1960 and 1970) were considered. Moulting process of primaries and secondaries is serially continuous, with several moult waves proceeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Despite being adults, they did not differ substantially from dispersing juveniles from the Czech Republic, Austria, and Hungary, who roamed over an area of 13, 376 km 2 (median 95% mcp) [29]. Ranging data suggested that immature eagles roamed relatively vast territories, but subadults in their fourth calendar year began seeking breeding territories, often in proximity to their natal sites, and some even initiated breeding attempts [17]. It is important to note that these findings were based on ringing recoveries from the period between 1977 and 2006, and the white-tailed eagle population is currently much more saturated, with young adults still in search of territories.…”
Section: Ranging Behavior Of Floatersmentioning
confidence: 87%
See 1 more Smart Citation
“…Despite being adults, they did not differ substantially from dispersing juveniles from the Czech Republic, Austria, and Hungary, who roamed over an area of 13, 376 km 2 (median 95% mcp) [29]. Ranging data suggested that immature eagles roamed relatively vast territories, but subadults in their fourth calendar year began seeking breeding territories, often in proximity to their natal sites, and some even initiated breeding attempts [17]. It is important to note that these findings were based on ringing recoveries from the period between 1977 and 2006, and the white-tailed eagle population is currently much more saturated, with young adults still in search of territories.…”
Section: Ranging Behavior Of Floatersmentioning
confidence: 87%
“…White-tailed eagles typically commence breeding in their fifth calendar year [15] and attain full adult plumage at that time [16]. However, owing to a substantial increase in their population numbers in recent decades [17][18][19], many adult individuals may still not establish territories, as the age of first reproduction is a density-dependent trait in avian predators [20]. This has led to an increase in the proportion of floaters in the population.…”
Section: Introductionmentioning
confidence: 99%
“…While nesting pairs are known to be sedentary, juvenile, immature, and non-breeding, floating adults [11] move over large parts of central and eastern Europe in the course of their natal dispersion [12], which typically lasts several years in this delayedmaturity species [13]. Several studies have examined the process of natal dispersal in whitetailed eagles, and have recorded details such as timing [14], distances travelled [15,16], habitat use [17], degree of fidelity to the natal area upon recruitment [18], and the potential of human-wildlife conflicts associated with wind energy [19]. White-tailed eagles begin their dispersal from July to October of their hatch year [12] and breed in their fourth calendar year at the earliest [20].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, flight feather renewal requires proportionately more time for large than for small birds because the growth rate of flight feathers increases only about half as fast as does the length of the flight feathers when these variables are scaled to body mass (Rohwer et al 2009). Thus, large birds that fly while moulting often carry some heavily worn feathers in their wings and tails (Struwe-Juhl & Schmidt 2003, Rohwer et al 2011.…”
mentioning
confidence: 99%
“…). Thus, large birds that fly while moulting often carry some heavily worn feathers in their wings and tails (Struwe‐Juhl & Schmidt , Rohwer et al . ).…”
mentioning
confidence: 99%